2022
DOI: 10.1093/jnci/djac188
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks by sex and variant type in PTEN hamartoma tumor syndrome

Abstract: BACKGROUND PTEN Hamartoma Tumor Syndrome (PHTS) is a rare syndrome with a broad phenotypic spectrum, including increased risks of breast (BC, 67-78% at age 60), endometrial (EC, 19-28%) and thyroid cancer (TC, 6-38%). Current risks are likely overestimated due to ascertainment bias. We aimed to provide more accurate and personalized cancer risks. METHODS A European, adult PHTS cohort study with data from medical files, regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Compared to previously reported rates [2,9,34,73,[75][76][77], recent literature suggests that PHTS patients may have an even higher risk of developing breast cancer (up to 80%) and endometrial cancer (up to 28%). In addition, these patients may develop a significant number of benign thyroid lesions (up to 60%) and thyroid cancer (over 10%) [34,78].…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Compared to previously reported rates [2,9,34,73,[75][76][77], recent literature suggests that PHTS patients may have an even higher risk of developing breast cancer (up to 80%) and endometrial cancer (up to 28%). In addition, these patients may develop a significant number of benign thyroid lesions (up to 60%) and thyroid cancer (over 10%) [34,78].…”
Section: Discussionmentioning
confidence: 57%
“…Compared to previously reported rates [2,9,34,73,[75][76][77], recent literature suggests that PHTS patients may have an even higher risk of developing breast cancer (up to 80%) and endometrial cancer (up to 28%). In addition, these patients may develop a significant number of benign thyroid lesions (up to 60%) and thyroid cancer (over 10%) [34,78]. Genetic and molecular studies of PHTS have revealed the presence of pathogenic variants in the PTEN/MMAC1 gene, located on chromosome 10 at position q 22-23, which is implicated in breast and thyroid cancer [73,[79][80][81][82].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations